The digital future of mechanical engineering: Assessing the potential for platform markets - V.E. Kovalev; N.Yu. Yaroshevich; O.V. Komarova (Управленец)
It is critically important for mechanical engineering in Russia to design a long-term development model capable of ensuring sustainable growth and profit and implementing the priorities of the policy on import substitution and technological sovereignty. Such a model can be discovered when integrating direct government regulation tools and modern digital platform solutions, which causes the transformation of the traditional industrial market into a platform one. The article presents theoretical substantiation and parametric assessment of the potential for platform markets formation in mechanical engineering in Russia. The theoretical framework combines the theories of two-sided (multi-sided) markets, industrial organization and matching mar ket design that promote the concept of platform markets. Dynamic, statistical and industry analysis were used as research meth ods. The evidence base covers data on three mechanical engineering markets in Russia for 2021–2023. Through theoretical analy sis, the study systematizes key features of a platform market and justifies a methodological approach to assessing the potential for implementing platform solutions that ensure the transformation of industrial market, including its structural and institutional indicators. The potential is evaluated based on the authors’ algorithm and calculations of its integral value. Testing was carried out using the case of mechanical engineering markets. They were empirically proven to have the potential for introduction of digital solutions and a platform-based type of coordination. The proposed method not only assesses a platform market’s development potential in the sub-sectors of mechanical engineering, but also serves as a tool for forming practices of state industrial policy, as well as choosing and justifying instruments for sustainable growth of industrial production.